Synthesis, characterization and applications of mixed-ligand copper(ii) complexes containing saccharin - Mohd Mokhtaruddin, Nur Shuhada (2016)
Eighteen tridentate Schiff bases derived from thiosemicarbazide were synthesized using various aldehydes and ketones via condensation reaction. Eighteen new mixedligand metal complexes were synthesized by reacting copper saccharinate with the appropriate Schiff bases in water-ethanol mixtures and have been characterized by elemental analysis and conductance, magnetic susceptibility, FTIR and electronic spectroscopic measurements. The complexes formed with general formula [Cu(sac)(NNS)]/[Cu(sac)(NNS)(H₂O)] or [Cu(sac)(ONS)]/[Cu(sac)(ONS)(H₂O)] where NNS and ONS are tridentate ligands. Magnetic and spectral evidence support a four or five-coordinate geometry for the complexes in which the Schiff bases coordinate to the Cu(II) ion as a uninegative charged tridentate ligand through the pyridine nitrogen or phenoxide oxygen atom, azomethine nitrogen atom and thiolate sulphur atom. The saccharinate anion coordinates as a unidentate N-donor ligand. The fifth coordination positions are occupied by the oxygen atom of the aqua ligand. The molar conductance results indicate that the metal complexes were non-electrolytes in DMSO solution. The cytotoxic activities of the complexes and the Schiff bases were evaluated against two breast cancer cell lines, MCF-7 (Estrogen Receptor Positive Human Breast Carcinoma Cells) and MDA-MB-231 (Estrogen Receptor Negative Human Breast Carcinoma Cells). Most of the complexes showed a higher potential compared than their ligands towards both cancer cell lines. The copper complexes were also deposited into copper oxide thin films by using Aerosol-Assisted Chemical Vapour Deposition technique and characterized by XRD and FESEM. The photocurrent activity of the copper oxide thin films was carried out but showed negative results.